Drainage in urban water environment - Babangida, Baba; Kueh, Meirilynna Cheing Ling; Rahimi, Nur Fatin Lyana; Jaafar, Nurul Nadiah; Md Saleh, Zubaidah (Penerbit UTHM, 2020)
Good drainage improves the waterways from the place of origin is released. However, improper waste management system in drainage could lead pollution in streams and rivers. In the case study in Batu Pahat town, there are several issues arise on drainage system. One of the main problems that caused the drainage get clogged is food waste from restaurants especially in closed drainage. There are several effects that are encountered if the waste management in the drainage system is poor. The effects could happen on human, flora and fauna, and environment. The aim of this chapter will identify the method of practices that has been used for cleaning the drainage. Responsibilities of local authorities in cleaning the drains at Batu Pahat will be explained. The best management practise to overcome the drainage pollution issues will be highlighted.